2015
DOI: 10.1183/09031936.00164714
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulant treatment for acute pulmonary embolism: a pathophysiology-based clinical approach

Abstract: The management of patients with acute pulmonary embolism is made challenging by its wide spectrum of clinical presentation and outcome, which is mainly related to patient haemodynamic status and right ventricular overload. Mechanical embolic obstruction and neurohumorally mediated pulmonary vasoconstriction are responsible for right ventricular overload. The pathophysiology of acute pulmonary embolism is the basis for risk stratification of patients as being at high, intermediate and low risk of adverse outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 63 publications
(63 reference statements)
0
14
0
Order By: Relevance
“…Our results are consistent with the Bova score, as a decreased systolic pressure (90-100 mmHg) and an elevated heart rate (≥ 110 beats/min) were risk factors for adverse outcomes. In normotensive patients with acute PE that is deteriorating, tachycardia and relative hypertension are compensatory and neurohumoral responses to a low left heart output [5,27,28]. However, we found that elevated NT-pro BNP concentrations were a signi cant risk factor, but elevated c-Tn I concentrations were not, which con icts with the 2019 ESC algorithm and Bova score.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Our results are consistent with the Bova score, as a decreased systolic pressure (90-100 mmHg) and an elevated heart rate (≥ 110 beats/min) were risk factors for adverse outcomes. In normotensive patients with acute PE that is deteriorating, tachycardia and relative hypertension are compensatory and neurohumoral responses to a low left heart output [5,27,28]. However, we found that elevated NT-pro BNP concentrations were a signi cant risk factor, but elevated c-Tn I concentrations were not, which con icts with the 2019 ESC algorithm and Bova score.…”
Section: Discussionmentioning
confidence: 57%
“…To expand the utility of our tools, we did not consider the underlying disease, which can predict a poor prognosis in acute PE [29]. In this context, elevated NT-pro BNP and c-Tn I concentrations are caused by myocyte stretching [27]. However, NT-pro BNP can re ect the patient's current state and also underlying disease, such as chronic heart failure [28,30], although c-Tn I concentrations do not.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are consistent with the Bova score as a decreased systolic pressure (90-100 mmHg) and an elevated heart rate (≥110 beats/min) were risk factors for adverse outcomes. In normotensive patients with acute PE that is deteriorating, tachycardia and relative hypertension are compensatory and neurohumoral responses to a low left heart output [26][27][28]. However, we found that elevated NT-pro BNP concentration was included in the nal scoring tool for predicting adverse outcomes, and c-Tn I concentration was not included.…”
Section: Discussionmentioning
confidence: 89%
“…11 Although systemic and catheter-directed anticoagulation has arisen as the treatment of choice for most cases of PE, the effectiveness of these approaches remains suboptimal in cases of massive PE. 3,12 Significant complications of anticoagulation and thrombolysis exist. These include hemorrhagic stroke, hemothorax, and hematoma with major bleeding episodes occurring in up to 20% of patients treated with these modalities.…”
Section: Discussionmentioning
confidence: 99%